2017
DOI: 10.1002/anie.201612185
|View full text |Cite
|
Sign up to set email alerts
|

19F‐NMR Reveals the Role of Mobile Loops in Product and Inhibitor Binding by the São Paulo Metallo‐β‐Lactamase

Abstract: Resistance to β‐lactam antibiotics mediated by metallo‐β‐lactamases (MBLs) is a growing problem. We describe the use of protein‐observe 19F‐NMR (PrOF NMR) to study the dynamics of the São Paulo MBL (SPM‐1) from β‐lactam‐resistant Pseudomonas aeruginosa. Cysteinyl variants on the α3 and L3 regions, which flank the di‐ZnII active site, were selectively 19F‐labeled using 3‐bromo‐1,1,1‐trifluoroacetone. The PrOF NMR results reveal roles for the mobile α3 and L3 regions in the binding of both inhibitors and hydroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…Previous work showed that the native sequence insertion of SPM-1 can adopt two conformations in equilibrium (24): one open conformation (SPM-1 open ) in which residues are arranged as an extension of the ␣3 helix and an additional ␣4 helix, both exposed and oriented toward the solvent (14), and one closed conformation, similar to B2 enzymes (SPM-1 closed ) ( Fig. 4) (24,25). The crystal structures of both forms were used as starting geometries for separate MD runs, both for the wild-type SPM-1 and the chimeric protein.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work showed that the native sequence insertion of SPM-1 can adopt two conformations in equilibrium (24): one open conformation (SPM-1 open ) in which residues are arranged as an extension of the ␣3 helix and an additional ␣4 helix, both exposed and oriented toward the solvent (14), and one closed conformation, similar to B2 enzymes (SPM-1 closed ) ( Fig. 4) (24,25). The crystal structures of both forms were used as starting geometries for separate MD runs, both for the wild-type SPM-1 and the chimeric protein.…”
Section: Resultsmentioning
confidence: 99%
“…SPM‐1 was selectively labeled at residue 152 on its α3 region, which forms part of the active site cleft, using cysteine alkylation by 3‐bromo‐1,1,1‐trifluoroacetone (BTFA) (Figure A) . The 19 F NMR spectrum of labeled SPM‐1 (SPM‐1 Y152C*) manifests two peaks assigned as corresponding to “closed” (−83.3 ppm) and “open” (−72.4 ppm) conformations of the α3 loop (Figure S5) . Addition of known MBL inhibitors (e.g., isoquinoline derivatives, 1,10‐ o ‐phenanthroline) results in line broadening and chemical shift changes in the 19 F NMR of α3 variants .…”
Section: Figurementioning
confidence: 99%
“…The 19 F NMR spectrum of labeled SPM‐1 (SPM‐1 Y152C*) manifests two peaks assigned as corresponding to “closed” (−83.3 ppm) and “open” (−72.4 ppm) conformations of the α3 loop (Figure S5) . Addition of known MBL inhibitors (e.g., isoquinoline derivatives, 1,10‐ o ‐phenanthroline) results in line broadening and chemical shift changes in the 19 F NMR of α3 variants . By contrast, titration of 1 with SPM‐1 Y152C* manifests only small effects on the SPM‐1 Y152C* 19 F NMR spectra (Figure S5).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…According to the catalytic mechanisms, β-lactamases are grouped into two catalogs: serine β-lactamases (SBLs, using the active site serine residue as a nucleophile) and metallo-β-lactamases (MBLs, using the Zn 2+ activated hydroxide as a nucleophile) [6][7][8]. Up to now, to circumvent bacterial resistance mediated by β-lactamases, five clinically useful SBL inhibitors have been developed, including clavulanic acid, sulbactam, tazobactam, avibactam, and vaborbactam [9][10][11][12]. In contrast, there remain no FDA-approved small-molecule inhibitors for MBLs, which can hydrolyze almost all β-lactam antibiotics, including the last-generation cephalosporins and carbapenems [13,14].…”
Section: Introductionmentioning
confidence: 99%